PENINGKATAN WAWASAN CYBER SECURITY AWARENESS DAN TEKNIK MELINDUNGI SMARTPHONE PADA TREN DIGITAL EKONOMI - Subektiningsih, Subektiningsih; Wulandari, Irma Rofni; Sekarningrum, Anggun Anindya; Hidayat, Muhammad Alfi; Baharudin, Muhamad (Jurnal Abdi Insani, 2024)
Partners are HNI Sleman business group members who use smartphones and social media in product marketing. In the process, they use internet connections and interact with various users. The use of technology has many benefits, but there are various gaps in cybercrime threats. Therefore, Partners need to understand the basics of cybersecurity and techniques to protect smartphones. This assistance aims to increase the Partners' insight or knowledge about cybersecurity related to data, information, and devices. The activity is conducted through training and the presentation of materials. In its implementation, a pre-test is carried out before training, and a post-test is carried out after training. To interpret the training results, the pre-test and post-test results will be calculated as an index value in %. The results show that HNI Sleman Partners' awareness level about cybersecurity after training was 98.75%. In this case, it is similar to a 70% increase in participants' knowledge about how to deal with cybercrime threats; before training, it was 28.75%, and after training, the level of participant insight became 98.75%. Meanwhile, participants’ knowledge of protecting smartphones was 95% after training. In this case, there was an increase of 37.5%, with the initial condition before the training being 57.5%. The training participants became aware of social engineering modes and cybercrime models and how to overcome them. Utilizing the security features available in smartphones and completing them by implementing 2FA, restricting application permission access, and good password management.